2008
DOI: 10.1007/s10333-007-0102-x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the dependence of the crop calendar for rain-fed rice on precipitation in Northeast Thailand

Abstract: Rain-fed lowlands are major agricultural ecosystems used for rice production in Northeast Thailand. Developing a tool to assess the effects of variable water conditions on the regional scale yield is also important to predict the effects of climate change on food supply. To estimate regional yields, we need a simple but accurate measure of the crop calendar (i.e., the distribution of planting dates), which has a strong influence on grain yield. In this article, we modeled the dependence of the crop calendar on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 15 publications
3
41
1
2
Order By: Relevance
“…In rain-fed production systems, insufficient early rainfall can force farmers to delay planting. Although data in Lao PDR are not available, Sawano et al (2008) studied the relationship between rainfall and planting dates in rain-fed areas of northeast Thailand, an area that is geographically similar to the central plains of Lao PDR. The authors concluded that, depending on field-level water availability from rainfall, planting dates were locally distributed over an approximately two-month period, while local harvesting took place around the same time everywhere.…”
Section: The Role Of Watermentioning
confidence: 99%
“…In rain-fed production systems, insufficient early rainfall can force farmers to delay planting. Although data in Lao PDR are not available, Sawano et al (2008) studied the relationship between rainfall and planting dates in rain-fed areas of northeast Thailand, an area that is geographically similar to the central plains of Lao PDR. The authors concluded that, depending on field-level water availability from rainfall, planting dates were locally distributed over an approximately two-month period, while local harvesting took place around the same time everywhere.…”
Section: The Role Of Watermentioning
confidence: 99%
“…Planting time also varies from field-to-field within each region. Frequency distribution of transplanting time within a target area is an effective means to improve model performance for regional-scale yield estimation (Stehfest et al 2007;Sawano et al 2008). Previously, we expressed a frequency distribution of planting time as a function of precipitation for the rain-fed lowland production system , but in the present study, because irrigated lowland is the most common system, we assumed a fixed normal distribution in each province with the initial and terminal dates given in Yan et al (2003).…”
Section: Phenology and Crop Calendarmentioning
confidence: 99%
“…Various types of crop phenology models have been developed and used in rice growth models (reviewed by Zhang and Tao 2013), but those used for a wide range of environmental conditions generally include functions of temperature and day length to account for photoperiod and temperature sensitivities Yin et al 1997;Sawano et al 2008). In these models, parameters are specific to each cultivar estimated from controlled-environment or field experiments.…”
Section: Phenology and Crop Calendarmentioning
confidence: 99%
“…Previous research on rice cultivation in Northeast Thailand reported that the timing of rice planting is highly dependent on the moisture condition of paddy surfaces, and that planting must be finished by the end of August to ensure that the plants do not reach the heading stage while immature (e.g., Sawano et al, 2008). Our results are consistent with those previous findings, and they suggest that the variability of the area of rice planted can be evaluated appropriately from the moisture condition of the land surface as estimated by our model.…”
Section: Saturated Area and Rice-planted Areamentioning
confidence: 99%
“…Most rice in Northeast Thailand is cultivated in rainfed lowland paddies that are not serviced by water management systems. In the rainfed lowland ecosystem, surface water conditions are very dependent on climatic conditions; therefore, rice production is vulnerable to climate variability, and especially variability in precipitation (e.g., Sawano et al, 2008;Goto et al, 2008). Therefore, it is important to clarify the practical relationships between rice productivity and climatic condition in this region concretely, in order to contribute sustainable food supply under the fluctuating climatic condition in Southeast Asia.…”
Section: Introductionmentioning
confidence: 99%